Control of physical conditions of students of special medical groups with disorders of the musculoskeletal system as a prerequisite for the development of programs of physical therapy - O. Z. Blavt; V. M. Koriahin; E. Yu. Doroshenko; L. I. Levchenko; S. H. Puzik; A. M. Hurieieva; O. Ye. Chernenko; M. O. Oliinyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose of the work is to investigate the effectiveness of the use of physical condition control of students of special medical groups for the development of physical therapy programs.